Leith on life. - Leith, Sam (Prospect, 2016)
The article offers the author's insights on the performance of their family computer, citing how it collapse while his wife is editing a video for her father's 70th birthday. Topics discussed include the unavailability of the storage memory of the computer which causes it to malfunction considering the family photographs they stored on its archive, how he considers photographing activities, and the implication of the introduction of smartphone to children.